Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10585-012-9531-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal stiffness, friction, and fluidity of cancer cell lines with different metastatic potential

Abstract: We quantified mechanical properties of cancer cells differing in metastatic potential. These cells included normal and H-ras-transformed NIH3T3 fibroblast cells, normal and oncoprotein-overexpressing MCF10A breast cancer cells, and weakly and strongly metastatic cancer cell line pairs originating from human cancers of the skin (A375P and A375SM cells), kidney (SN12C and SN12PM6 cells), prostate (PC3M and PC3MLN4 cells), and bladder (253J and 253JB5 cells). Using magnetic twisting cytometry, cytoskeletal stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 74 publications
6
82
0
4
Order By: Relevance
“…In contrast, analysis of cells in suspension or nonspread cells would be expected to mainly detect stiffness of the cortical cytoskeletal network and the cell nucleus. In agreement with this, previous reports have indicated that cell spreading is a main determinant of the cell stiffness that is detected (45).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, analysis of cells in suspension or nonspread cells would be expected to mainly detect stiffness of the cortical cytoskeletal network and the cell nucleus. In agreement with this, previous reports have indicated that cell spreading is a main determinant of the cell stiffness that is detected (45).…”
Section: Discussionsupporting
confidence: 91%
“…The mechanical properties of cells are closely related to a number of biological functions, such as cell differentiation, aging, motility, metastasis, and mechanotransduction [14]. Several studies have recently suggested that cellular properties can be utilized as label-free biomarkers for disease diagnosis [57].…”
Section: Introductionmentioning
confidence: 99%
“…Another biomechanical screening approach in the adherent cell is the magnetic twisting cytometry, a commonly used technique to screen for impacts on cell stiffness [9294]. During magnetic twisting cytometry measurements, ferromagnetic beads (4.5 μm in diameter) are tightly anchored to the cell cytoskeleton and oscillated using a known magnetic field (5–75 Gauss).…”
Section: Selected Bioassays For Use In Mechanopharmacologymentioning
confidence: 99%